Rancang Bangun Sistem Monitoring Tugas Akhir Berbasis Web: Sistem Monitoring Tugas Akhir - Andini Septiani; Muhammad Ikhwan; Asa Hari Wibowo (Jurnal Informatika Ilmu Komputer dan Sistem Informasi, 2023)
The Final Assignment Monitoring System (SIMTAR) is an online platform that is used to manage and monitor the progress of student final assignment work effectively and efficiently [1]. In lectures, making a final assignment is one of the important things and is mandatory for students to complete at the end of their study period. Due to the large number of students who work on their final assignments every year, supervisors must be more careful in supervising these students. Therefore, as a solution to increase the effectiveness and efficiency of the student supervision process, a system was created using a prototype method called the Final Assignment Monitoring System (SIMTAR) which aims to facilitate supervision, coordination and communication between students, supervisors and other related parties in evaluation process when working on students' final assignments. The result of this research is that a system is obtained that can work well and can meet the needs of the Informatics Engineering Department, Halu Oleo University.